2014
DOI: 10.1007/s13197-014-1564-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of raspberry (Rubus fruticosus) leaves extract and its effect on oxidative stability of sunflower oil

Abstract: Efficacy of R. fruticosus leaves extract in stabilizing sunflower oil during accelerated storage has been studied. Extracts of R. fruticosus were prepared in different solvents which methanolic extract yield with 15.43 % was higher than water and acetone ones (11.87 and 6.62 %, respectively). Methanolic extract was chosen to evaluate its thermal stability at 70°C in sunflower oil, due to the highest yield, antioxidant and antiradical potential and also high content of phenolic compounds campared to other solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 28 publications
2
31
1
4
Order By: Relevance
“…Asnaashari et al . () also found that the AAI values of the treated samples with 200, 400, 600, 800 and 1000 ppm of R. fruticosus extract were 1.013, 1.07, 1.187, 1.47 and 2.09, respectively, suggesting its remarkable effectiveness on oxidative stability of sunflower oil.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Asnaashari et al . () also found that the AAI values of the treated samples with 200, 400, 600, 800 and 1000 ppm of R. fruticosus extract were 1.013, 1.07, 1.187, 1.47 and 2.09, respectively, suggesting its remarkable effectiveness on oxidative stability of sunflower oil.…”
Section: Resultsmentioning
confidence: 77%
“…After the 6th day, there was a sharp rise in PV of control sample from 8.35 to 75.74 meqO 2 kg −1 oil. However, PV s of the samples with 1000 ppm of the methanolic extract changed from 1.8 (at day 6) to 18.8 meqO 2 kg −1 oil (at day 12) (Asnaashari et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In the propagation stage, the peroxide value increased rapidly and the amount of lipid hydroperoxides accumulated to an extremely high level. After the peroxide content reached a maximum level in the Kilka oil, the rate of peroxide decomposition actually exceeded the rate of formation, resulting in deceasing peroxide value . The level of hydroperoxides in the Kilka oil samples increased relatively slowly towards the end of induction period (the PV IP values ranged from 9 meqO 2 kg) −1 to 31meqO 2 (kg) −1 for gallic acid and to 40 meqO 2 (kg) −1 for methyl gallate) and then increased sharply in the propagation stage of lipid oxidation.…”
Section: Resultsmentioning
confidence: 96%
“…Na taką ich zdolność wskazują również bada nia innych autorów z wykorzystaniem liści miłorzębu [13,14,15,23,24], a także badania przeprowadzone na liściach innych roślin, w tym np. winorośli właściwej [25], aronii czarnej [26], akki sellowej [27], bielunia surmikwiatu [28] czy jeżyny euro pejskiej [29].…”
Section: Dyskusjaunclassified